Formulation and Evaluation of Sustained Release Matrix Tablets of Aceclofenac - Priyanka Singh; Amit Kumar Shrivastava; Sachin Kumar; Manish Dhar Dwivedi (Borneo Journal of Pharmacy, 2021)
This study aimed to improve the dissolution rate of aceclofenac and release the drug in a controlled manner over a period of 24 hours. Matrix tablets were prepared by direct compression method, using hydrophilic polymers (HPMC/guar gum). Matrix tablets were prepared by wet granulation method using different hydrophilic polymers (HPMC/guar gum). Tablets were evaluated for in vitro drug release profile in phosphate buffer with pH 6.8 (without enzymes). The thickness and hardness of prepared tablets were 3.23 ± 0.035 to 3.28 ± 0.008 mm and 3.26 ± 0.115 to 3.60 ± 0.200 kg/cm2, respectively. The friability was within the acceptable limits of pharmacopoeial specifications (0.31 to 0.71%), which indicates the good mechanical strength of the tablets. Drug release was retarded with an increase in polymer concentration due to the gelling property of polymers. The in vitro drug release from the proposed system was best explained by Higuchi’s model, indicating that drug release from tablets displayed a diffusion-controlled mechanism. The results clearly indicate that guar gum could be a potential hydrophilic carrier in developing oral controlled drug delivery systems. Based on the study results, formulations F8 was selected as the best formulation.